2023
DOI: 10.1186/s12909-023-04033-6
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Medical Education Research Study Quality Instrument (MMERSQI) developed by Delphi consensus

Abstract: Background The Medical Education Research Study Quality Instrument (MERSQI) is widely used to appraise the methodological quality of medical education studies. However, the MERSQI lacks some criteria which could facilitate better quality assessment. The objective of this study is to achieve consensus among experts on: (1) the MERSQI scoring system and the relative importance of each domain (2) modifications of the MERSQI. Method A modified Delphi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…5-point rating scale as follows: “1 = very uncomfortable,” to “5 = very comfortable.” Pre/ Post session All medical students 2018–20 ( n = 152) How comfortable are you talking to patients about issues related to sexuality? ‘Very confident’ - TG 29% [ 22 , 36 ]/ 68%[59,77]; LGBT 49% [ 41 , 57 ]/ 84%[77,91]; How comfortable are you discussing with patients? Medical Transition 22% [ 15 , 28 ]/ 57% [ 48 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-point rating scale as follows: “1 = very uncomfortable,” to “5 = very comfortable.” Pre/ Post session All medical students 2018–20 ( n = 152) How comfortable are you talking to patients about issues related to sexuality? ‘Very confident’ - TG 29% [ 22 , 36 ]/ 68%[59,77]; LGBT 49% [ 41 , 57 ]/ 84%[77,91]; How comfortable are you discussing with patients? Medical Transition 22% [ 15 , 28 ]/ 57% [ 48 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the studies was assessed by two reviewers, using the Medical Education Research Study Quality Instrument (MERSQI) [ 40 , 41 ]. The MERSQI was developed to appraise methodological quality in medical education research and is suitable, reliable and simple to use.…”
Section: Methodsmentioning
confidence: 99%
“…This step was essential to de ne the research question and appropriately review the data found. The second part employed a six-step approach to scoping reviews (10), which included appraising the methodological quality of the articles using the modi ed Medical Education Research Study Quality Instrument (MMERSQI) (11) and the CNA-Chile criteria for medical specialty programs (7). At least two independent researchers conducted each step of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the studies quality was carried out using MERSQI (Medical Education Research Study Quality Instrument) Study quality was assessed using the Medical Education Research Quality Instrument (MERSQI) for quantitative studies, which is a validated tool widely used in education research. 22 , 23 This quality assessment tool comprises six domains: “study design,” “sampling,” “type of data,” “validity of evaluation instrument,” “data analysis,” and “outcomes.” The minimum score within five of the domains is = 1, and the maximum score across all domains is = 3. Accordingly, MERSQI scores range from 5 to 18.…”
Section: Methodsmentioning
confidence: 99%